2022
DOI: 10.1103/physrevapplied.17.034044
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Transport Modeling, Design Principles, and Empirical Rules for Low-Noise III-V Digital-Alloy Avalanche Photodiodes

Abstract: A series of III-V ternary and quarternary digital alloy avalanche photodiodes (APDs) have recently been seen to exhibit very low excess noise. Using band inversion of an environment-dependent atomistic tight binding description of short period superlattices, we argue that a combination of increased effective mass, minigaps and band split-off are primarily responsible for the observed superior performance. These properties significantly limit the ionization rate of one carrier type, either holes or electrons, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Accurate band structures of unstrained and strained bulk III–V materials/alloys were used as fitting targets for our model. We have previously demonstrated that our model can match hybrid functional band structures of bulk, strained, and superlattice systems. ,, …”
Section: Band Structure Simulationmentioning
confidence: 92%
See 1 more Smart Citation
“…Accurate band structures of unstrained and strained bulk III–V materials/alloys were used as fitting targets for our model. We have previously demonstrated that our model can match hybrid functional band structures of bulk, strained, and superlattice systems. ,, …”
Section: Band Structure Simulationmentioning
confidence: 92%
“…The tuning of width, composition, and asymmetry of the MQW structure enables deterministic optical and electronic material parameters. The widely reported digital alloys (DAs) are essentially a short-period, multicomponent generalization of superlattices, where the superlattice period is reduced sufficiently that charge carrier wave functions integrate over many periods. They can improve the performance of optoelectronic devices, for example, circumventing the limitations imposed by miscibility gaps, , engineering novel band structures, and providing a new method to achieve band gap tunability. , For example, the limitations imposed by the miscibility gap encountered in the random alloy (RA) growth of Al x In 1– x As y Sb 1– y lattice-matched to GaSb have been solved by using the DA growth technique. , In addition to the investigation of Sb-based quaternary alloys, the DA growth technique can significantly modify the material characteristics of In 0.52 Al 0.48 As (hereafter InAlAs) and In 0.53 Ga 0.47 As (hereafter InGaAs) ternary materials lattice-matched to InP. The reduction of the excess noise in DA InAlAs avalanche photodiodes (APDs) has been experimentally and theoretically demonstrated. , Compared to conventional RA InAlAs, wide band gap tunability is also obtained for DA InAlAs with different periodic structures .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to gain insight into the origin of low noise in Sb-based APDs, S. K. Ahmed et al [21] studied the AlInAsSb alloy valence band carrier transport using non-equilibrium Green's functions and Boltzmann transport equation formalisms. Their analysis showed that when the minigaps and the light-hole split-off energy gap are sufficiently large, they create barriers that are improbable to be overcome by quantum tunneling or phonon scattering processes.…”
Section: Alxin1-xasysb1-y P-i-n Structure Apdsmentioning
confidence: 99%